Physical activity levels in children with esophageal atresia and congenital heart disease: a comparative multicenter study - Frankenbach, Luisa Maria; Holler, Anne-Sophie; Sochaczewski, Christina Oetzmann von; Wessel, Lucas; Muensterer, Oliver; Dingemann, Jens; Widenmann, Anke; Helm, Paul; Siaplaouras, Jannos; Bauer, Ulrike; Apitz, Christian; Niessner, Claudia; et al. (European journal of pediatric surgery, 2025)
Aim of the Study Esophageal atresia (EA) is associated with impaired motor development, cardiopulmonary function, and physical activity (PA). Despite missing scientific evidence, this fact is often attributed to associated congenital heart disease (CHD). The aim of this study was to investigate PA in EA patients without CHD compared with CHD patients and healthy controls. Methods In this multicenter study, EA patients aged 6 through 17 years were included. Moderate-to-vigorous PA (MVPA, minutes per week) was assessed using the standardized and validated questionnaire Motorik-Modul Physical Activity Questionnaire. EA patients were randomly matched 1:4 for gender and age with patients with CHD (n = 1,262) and healthy controls (n = 6,233). Patients born with both EA and CHD were excluded. Means and 95% confidence intervals (95% CIs) were calculated. To identify associated factors, Spearman's correlation was performed. Main Results Overall, 69 EA patients were matched with 276 CHD patients and 276 controls (57% male, 43% female, mean age 10,3 years, 95% CI: 9.5-11.1). Mean MVPA was reduced in EA (492 minutes, 95% CI: 387-598) and CHD patients (463 minutes, 95% CI: 416-511) compared with controls (613 minutes, 95% CI: 548-679). In subgroup analysis, MVPA was reduced further in females and older age groups with EA and CHD. For EA patients, there was no statistical association between Gross type, current symptoms, surgical approaches, and MVPA.Conclusion Isolated EA and CHD were associated with reduced PA, especially in females and teenagers. To avoid additional morbidity associated with sedentary behavior, PA should be promoted during follow-up.
Online verfügbar: 28. Oktober 2024
Gesehen am 01.04.2025